Helper-Like Type-1 Innate Lymphoid Cells in Inflammatory Bowel Disease - Coman, Diana; Coales, Isabelle; Roberts, Luke B.; Neves, Joana F. (Frontiers in Immunology, 2022)
Inflammatory Bowel Disease (IBD) is an idiopathic condition characterised by chronic relapsing inflammation in the intestine. Whilst the precise aetiology of IBD remains unknown, genetics, the gut microbiome, environmental factors, and the immune system have all been shown to contribute to the disease pathophysiology. In recent years, attention has shifted towards the role that Innate Lymphoid Cells (ILCs) may play in the dysregulation of intestinal immunity observed in IBD. ILCs are a group of heterogenous immune cells which can be found at mucosal barriers. They act as critical mediators of the regulation of intestinal homeostasis and the orchestration of its inflammatory response. Despite helper-like type-I ILCs (ILC1s) constituting a particularly rare ILC population in the intestine, recent work has suggested that an accumulation of intestinal ILC1s in individuals with IBD may act to exacerbate its pathology. In this review we summarise existing knowledge on helper-like ILC1 plasticity and their classification in murine and human settings. Moreover, we discuss what is currently understood about the roles that ILC1s may play in the progression of IBD pathogenesis.